Express in simplest radical form. \[ \begin{array}{l}-4 \sqrt{6}+\sqrt{24}\end{array} \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
To simplify the expression \(-4 \sqrt{6} + \sqrt{24}\), we first simplify \(\sqrt{24}\). We can break down \(\sqrt{24}\) as follows: \[ \sqrt{24} = \sqrt{4 \cdot 6} = \sqrt{4} \cdot \sqrt{6} = 2\sqrt{6}. \] Now, we substitute this back into the original expression: \[ -4 \sqrt{6} + \sqrt{24} = -4 \sqrt{6} + 2\sqrt{6}. \] Next, we can combine the like terms: \[ -4 \sqrt{6} + 2\sqrt{6} = (-4 + 2) \sqrt{6} = -2\sqrt{6}. \] Thus, the expression in its simplest radical form is: \[ \boxed{-2\sqrt{6}}. \]